2021
DOI: 10.1007/s40744-021-00344-6
|View full text |Cite
|
Sign up to set email alerts
|

Pain Medication and Corticosteroid Use in Ankylosing Spondylitis, Psoriatic Arthritis, and Rheumatoid Arthritis in the United States: A Retrospective Observational Study

Abstract: Objective: We compared pain medication use in patients with ankylosing spondylitis (AS), psoriatic arthritis (PsA), and rheumatoid arthritis (RA) versus matched control over 2 years; a subgroup analysis assessed changes in pain medication use in patients who initiated a biologic during 12 months before and after. Methods: This was a retrospective observational cohort study using an administrative claims database. Newly diagnosed adult patients with AS, PsA, or RA identified between 1/1/2014 and 7/31/2017 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Chronic opioids are prescribed to 17% to 67% of US patients with RA. The highest recent estimate is from a study of Social Security Disability Insurance beneficiaries less than 65 years of age (Table 1) [6 ▪ –8 ▪ ,9 ▪▪ ,10–14]. A cross-sectional study of the National Ambulatory Medical Care Survey examining data from 2011 to 2016 showed that one-fourth of US office visits for RA involved an opioid prescription; opioid prescribing for outpatient RA visits increased from 15% to 34% ( P < 0.0001) over the time frame; and primary care physicians were the most common prescribers [6 ▪ ].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 3 more Smart Citations
“…Chronic opioids are prescribed to 17% to 67% of US patients with RA. The highest recent estimate is from a study of Social Security Disability Insurance beneficiaries less than 65 years of age (Table 1) [6 ▪ –8 ▪ ,9 ▪▪ ,10–14]. A cross-sectional study of the National Ambulatory Medical Care Survey examining data from 2011 to 2016 showed that one-fourth of US office visits for RA involved an opioid prescription; opioid prescribing for outpatient RA visits increased from 15% to 34% ( P < 0.0001) over the time frame; and primary care physicians were the most common prescribers [6 ▪ ].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Furthermore, different studies have shown that opioid use only modestly decreased after initiation of biologic therapies (Table 2). The most recent publication on this topic found that although opioid use significantly decreased 12 months after RA patients initiated biologic medications, the overall prevalence of opioid use remained high at 40% [9 ▪▪ ]. It is unknown whether these patients use opioids after biologic initiation because of persistent inflammatory disease activity not sufficiently controlled on therapy, persistent pain not due to active RA, patient reluctance to stop opioids, or lack of physician initiative to taper opioids after initiating biologic therapy.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 2 more Smart Citations
“…There are recent studies from different regions of the world revealing the real-world usage of NSAIDs in SpA. In a retrospective, observational study representing nationwide administrative claims data from the USA which included 2180 patients with AS and 5681 patients with PsA, at diagnosis NSAIDs were prescribed in 43.0% of patients with AS and 39.0% of patients in PsA, both significantly higher than matched controls [18]. Another study evaluated the primary care analgesia prescribing in English National Health Service-managed patients with inflammatory arthritis [19].…”
Section: Nonsteroidal Anti-inflammatory Drugs In Spondyloarthritismentioning
confidence: 99%